A Review of Symbolism in Indigenous West African Textiles (Journal of Science and Technology, 2016)
West African textiles form an important aspect of African art. Their uniqueness in the sense of symbolism reflects in their cultures and many forms of art and design. This paper traces some paths through the complex and still largely un-researched history of African textile artistry. It will explore some of the ways in which cloth has been and remains important in a selection of African societies, prominent among them West African textile art. It will introduce some of the major designs that have flourished in the C 20th, those which are both cherished in their local context and increasingly sought after by collectors and museums world-wide. Finally, the picture will be brought up to date through a consideration of the role of cloth traditions in contemporary dress and fashion design.